Development of Integrated Technology of Collection and Recycling of Plastic in Small Towns - MUKHAMADEYEVA, Railya M.; BAYAZITOVA, Zulfiya E.; ELYUBAEV, Sagintai Z.; MAKEYEVA, Ludmila A.; NURMAGANBETOV, Zhanmyrza O. (Journal of Environmental Management and Tourism; Vol 9 No 7 (2018): JEMT Volume IX Issues 7(31) Winter 2018DO - 10.14505//jemt.v9.7(31).01, 2019)
The developed version of the integrated technology for collection, sorting and processing of plastic bottles is recommended for settlements with a population not exceeding 50,000 people, with the prospect of separate collection of solid household waste and the prospect of consumption of products in plastic containers on average not less than 7 bottles per month per person. The proposed integrated technology for the collection and cryogenic crushing of PET containers, as studies have shown, is the most acceptable and effective for the Akmola region. The model for the installation of cryogenic grinding of PET containers requires further design work and the filing of documents for obtaining a patent. Focusing on the diversification of the economy of Kazakhstan, the existing enterprises for the collection and recycling of waste can independently deal with the output of end products in the form of threads, packaging or any other consumer goods.